Strategy of Education Boarding Raudhatul Ulum Lumajang in the Form of Life Entrepreneurship Santri - Zarkasyi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article results from field research that reveals the educational strategy of the Raudhatul Ulum Lumajang Islamic Boarding School so that students have a spirit of entrepreneurship. In this study, data analysis was carried out since data collection as a whole was rechecked. The research results conclude; The strategy is carried out in four dimensions: first, the mental independence of the santri is instilled in them being diligent, including in terms of managing finances. The second strategy is to bring in experts in the agribusiness field, Third by introducing business units in the agribusiness sector. The goal is to let students know what business units are around the pesantren because many pesantren business units are located in Sumberanyar villages. So that it can be a reference for opening a business after graduating from the pesantren. The fourth strategy is by providing apprenticeship opportunities to participate in managing the business units owned by the pesantren . From there, the creativity and innovation of students in experimenting with presenting their ideas to the teacher / ustadz. Keywords: strategy. Education, Islamic Boarding Schools, Entrepreneurship, Santri